Analisis Pengaruh e-Banking Terhadap Pelayanan dan Kemudahan Perbankan Syariah dalam Bertransaksi (Studi Kasus Masyarakat Kota Medan) - Muhammad Ridwan; Hutagalung , Muhammad Abrar Kasmin (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2020)
This study aimed to study and analyze. the effect of e-banking on the service and convenience of Islamic banking in the transaction for the people of Medan City. The method used in this research was a quantitative approach using data in the form of numbers, using multiple linear regression analysis and Islamic values ​​in using e-banking services and ease of transactions, supported by statistical tests, using the version-20-SPSS program. The research conducted simultaneously shows that this research has an F-count greater than the F-table or 33.791 > 2.47. Partially testing the e-banking coefficient, there is an effect of making transactions of 2.405. There is an effect of service coefficient in making transactions of 3,352. The coefficient of convenience has an effect in making transactions of 2,610. Therefore simultaneously and partially there is an effect of e-banking on services and convenience of transacting for the people of Medan City.